Can Achyranthes Aspera Be Used In Dentistry? - Anu Iswarya Jaisankar, Jayalakshmi Somasundaram, D. Ezhilarasan (Indian Journal of Forensic Medicine & Toxicology, 2020)
Plant kingdom serves the best source of remedy for all sorts of problems of the human body. Microbial speciesthat are found in almost every habitat present in nature accounts for about 60% of the Earth’s total biomass.The World Health Organisation (WHO) has stated that more than 80% of the people in the world rely upontraditional medicines for their primary treatment. On that note Achyranthes aspera commonly called as chaffflower has got immense therapeutic values. Each and every part of the plant, most importantly it’s seeds,roots and shoots possess great medicinal values. Achyranthes aspera belongs to the family Amaranthaceae.The Plant is a stiff erect annual herb. Achyranthes aspera has been used as a folk medicine in Australia, Indiaand Kenya It is useful in treating cough, renal dropsy, fistula, scrofula, skin rash, nasal infection, chronicmalaria, impotence, fever, asthma, piles and snake bites. Their stem parts can be used as an emmenagogue,anti arthritic, laxative, ecbolic, abentifacien, anti helminthic, antiviral, anti plasmodic, anti hypertensive, anticoagulant, diuretic and anti tumor agent. The ash from the burnt plant can be mixed with mustard oil anda pinch of salt and the tooth powder obtained is useful in cleaning teeth, treating pyorrhea and tooth ache.Their roots can also be powdered and used as a tooth powder and the roots itself were used as brushes. InIndia and Terai of Nepal, the juice of the plant is applied to relieve toothache. The stem of the plant was alsoused as a toothbrush after removing the thorns. The infusion of the twig is also used as a wash for tooth pain.Their usage in dentistry is remarkable as it has got good anti-cariogenic properties and anti inflammatoryproperties which has been discussed in detail in the current review article.